Predicting demand: the technique fundamentals - Mentzer, John T. (Henry Stewart Talks, 2010)
Series outline, The sales forecasting process, Role of techniques in forecasting accuracy, Time series techniques, Error plots, Where to look for the right time series technique, What time series does and does not do well, Regression analysis, The concept of R2, What regression analysis does well, Qualitative analysis, Qualitative forecasting approaches, What qualitative analysis does and does not do well, Conclusion